Upper Middle-Class Muslims and Market-Oriented Umroh Program Dissemination on Social Media - Triantoro, Dony Arung; Basri, Bifa Fanisa; Abadi, Mansurni (Idarotuna, 2023)
The emergence of upper middle-class Muslims in Indonesia does display not only religious piety on the one hand but also new consumption patterns on the other. This change in new consumption patterns simultaneously influences Islamic business people to manage their business activities in new ways oriented to market logic. This article discusses the market-based Umroh program in contemporary Indonesia. Based on nethnographic work on social media, this study found that the Umroh business captures economic opportunities from the identity and lifestyle of upper-middle-class Muslims. For middle and upper-class Muslims in Indonesia, pilgrimage to the holy land is a matter of worship and an experience to enjoy other countries, which are their modern identities. Umroh businesses capture this Islamic expression to provide umroh services and tours to visit countries in Asia, Europe, and the Middle East. In addition, this Umroh program is massively distributed through their social media channels.